Diagnostic dilemmas due to fish bone ingestion: Case report & literature review - Beecher, Suzanne M. (Int J Surg Case Rep, 2015)
INTRODUCTION: The diagnosis of abdominal complications due to fish bone ingestion is particularly difficult as the presentation may mimic common abdominal pathologies. PRESENTATION OF CASE: 65 year-old male presented with a two day history of right iliac fossa pain. He denied any nausea and vomiting. He had no systemic systems including fever, change in bowel habit. He had tenderness and guarding localized to the right iliac fossa. He had raised inflammatory markers. A CT scan of the abdomen was performed which showed fat standing in proximity to the terminal ileum, with the appearance of Crohn’s disease. The clinical picture did not match the imaging and so the patient underwent a diagnostic laparoscopy. Findings included an acutely inflamed terminal ileum. A foreign body was identified piercing through at the small bowel wall at the terminal ileum. The foreign body was removed and revealed a fish bone. Intracorporeal sutures were inserted at the site of the microperforation. The patient was discharged well two days post operatively. DISCUSSION: Fish bone perforation is not a common cause of gastrointestinal perforation. Unfortunately the history is often non-specific and these people can be misdiagnosed with acute appendicitis & other pathologies. CT scans can be useful to aid diagnostics. It is not however fully sensitive in detecting complications arising from fishbone ingestion. CONCLUSION: Management therefore, should be based taking into account primarily the clinical picture & may necessitate diagnostic laparoscopy.